A time to reap, a time to sow: Mitophagy and biogenesis in cardiac pathophysiology. (January 2015) - Andres, Allen M.; Stotland, Aleksandr; Queliconi, Bruno B.; Gottlieb, Roberta A.
Abstract: Balancing mitophagy and mitochondrial biogenesis is essential for maintaining a healthy population of mitochondria and cellular homeostasis. Coordinated interplay between these two forces that govern mitochondrial turnover plays an important role as an adaptive response against various cellular stresses that can compromise cell survival. Failure to maintain the critical balance between mitophagy and mitochondrial biogenesis or homeostatic turnover of mitochondria results in a population of dysfunctional mitochondria that contribute to various disease processes. In this review we outline the mechanics and relationships between mitophagy and mitochondrial biogenesis, and discuss the implications of a disrupted balance between these two forces, with an emphasis on cardiac physiology. This article is part of a Special Issue entitled "Mitochondria: From Basic Mitochondrial Biology to Cardiovascular Disease". Graphical abstract: Highlights: The role of mitophagy and biogenesis in the heart are discussed. Mitochondrial quality control depends on balanced mitophagy and biogenesis. Factors regulating these processes are summarized. Mitochondrial turnover is discussed in the context of heart disease. Major open questions are enumerated.